Recycled Aluminium Composite Pulley - Mazlee, Mohd. Noor; Shamsul Baharin, Jamaludin, Prof. Dr.; Murizam, Darus (Malaysian Invention & Design Society (MINDS), 2010)
Mazlee Mohd Noor and his team won silver at 17th International Invention, Innovation & Technology Exhibition 2006 (ITEX 2006), 19th - 21st May 2006 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.